Penerapan Pregnancy Music (Classic) terhadap Tingkat Kecemasan Ibu Hamil Trimester Iii di BPM Kristin Kota Batam Kepulauan Riau Tahun 2024 - Maria Hestina Nona Yeni; Vitalia Hanako Murni Simanjuntak; Juliana Munthe; Markus Doddy Simanjuntak (STIKES Columbia Asia Medan, 2024)
According to Mulyani (2018) breast self-examination (BSE) is a breast examination to find abnormal lumps. This examination can be done yourself without having to go to the health center and without having to pay any money. Based on data from the World Health Organization (WHO), the total number of cancer cases in Indonesia in 2020 reached 396,914 cases and the total deaths were 234,511 cases. Cancer prevalence in Indonesia in 2020 was dominated by breast cancer, with 65,858 cancer sufferers (16.6%). The research design used is an analytical type of research to determine the causal relationship between two variables. with a cross sectional approach where data collection for independent variables and dependent variables is carried out at one time only. The population of this study is all teenagers in the Rohana am.keb midwife clinic area. as many as 35 teenagers. The entire research population was used as a sample, data obtained from primary data was analyzed using the chisquare test. Based on the statistical test table, it can be seen that from the chi square test, Knowledge (P=value=0.007) is smaller than sig α (0.05). It is hoped that health workers will pay more attention to young women about the dangers of breast cancer.